Terahertz joint communication and sensing waveform:status and prospect - Zhiqing WEI; Zhiyong FENG; Yiheng LI; Hao MA; Jinzhu JIA (Tongxin xuebao)
To meet the requirements of machine communication and immersive service in the 6G era for high precision perception and high speed communication, communication perception integration technology emerges at the right moment.Based on this, the scenarios, waveform design methods and future prospects of terahertz communication perception integrated waveform were described and summarized.First of all, the scenarios and requirements of terahertz integrated waveform design were summarized, including perception-assisted communication scenarios, new business scenarios generated by perception, etc.Then, from the propagation characteristics of terahertz electromagnetic wave, the characteristics of terahertz devices, and the requirements of communication and perception on waveform, the characteristics of terahertz communication and perception integrated waveform were analyzed, and the research status of terahertz communication integrated waveform was summarized.Finally, the future research direction of terahertz synesthesia integrated waveform was pointed out.